Differences of the weighted differentiation composition operators from mixed-norm spaces to weighted-type spaces - Chen, Cui; Zhou, Ze-Hua (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We characterize the boundedness and compactness of the differences of weighted differentiation composition operators$D^n_{φ_1, u_1} - D^n_{φ_2, u_2}$, where $n \in N_0, u_1, u_2 \in H(D)$, and $φ_1, φ_2 \in S(D)$, from mixed-norm spaces $H(p, q, φ)$, where $0 < p,\; q < ∞$ and φ is normal, to weighted-type spaces $H^{∞}_v$.